The Differences of Student's Learning Outcomes and Instructional Interactions between Project Based Learning and Problem Based Learning Methods by Using Web Based Learning Technique in the Course of Videography at SMKN 1 Purwosari - Robherta, Miftachul; Dwi Herlambang, Admaja; Hadi Wijoyo, Satrio (Journal of Information Technology and Computer Science, 2021)
Learning activities during the COVID-19 pandemic has been making students are not able to be active than before the pandemic, and their learning outcomes somehow become less than optimal. This phenomenon tends to happen because the teachers only deliver the course material briefly then give assignments to students in the end of online class session. Therefore, this present study aimed to analyze the differences of students' learning outcomes and instructional interaction on the course of Videography by applying the method differences of PjBL with PBL. This present study applied Quasi Experiment research method by using Nonequivalent Control Group Design. The subject of this present study involved students of grade XI from department of Visual Communication Design, SMK Negeri 1 Purwosari. Hence, its research sample was categorized as population member since there was only one group within the class of DKV Department. Furthermore, the data collection techniques included questionnaire non test of instructional interaction and test results of learning questions pre test and post test. This present study also applied independent t test as the data analyzing technique. Eventually, the results showed that PjBL method was more appropriate in term of learning outcomes than PBL method in which it was evidenced with the hypothesis test result was less than significant level of 0.05. Additionally, PBL was more appropriate in term of instructional interaction than PjBL method that was showed by hypothesis test result which was less than significant level of 0.05.